Evaluasi Peran Kepemimpinan Dalam Meningkatkan Mutu Pendidikan di Pesantren Qur’an Al Fida - Ahmad Baihaqi M; Minallahi Ramadhan; Edi Ahmadi (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Leadership has experienced difficult roles such as educators, managers, administrators, supervisors, and motivators in improving the quality of education, characterized by difficulties recruiting new students even schools are closed or schools disband. The purpose of this study is to evaluate the role of leadership in improving the quality of education in Pesantren Qur'an Al Fida. Using descriptive-qualitative methods, with a CIPP (Context, Input, Process and Product) model approach. Primary data sources obtained through direct observation in the field, and secondary data obtained through pesantren leadership report documents, representatives, teachers, and pesantren administration personnel through interviews, observations, and documentation. Data analysis using library research, by studying, collecting and processing data from various literature sources, both journals and books. The results of the study concluded that the evaluation of the role of leadership in improving the quality of education in the Qur'an Al-fia Islamic Boarding School. The contex stage has been carried out its leadership role. The input stage of pesantren leaders has a good influence, namely, providing life examples, paying attention, developing the potential of education staff and teachers, through education and training both seminars, workshops, webinars, providing motivation and a better vision and mission for the future. At the stage of the process, pesantren leaders make adjustments between programs that have been planned to improve the quality of education including improving teacher performance, involving students. The product stage, has implemented a teacher performance improvement program, comfortable learning for students, so that students excel both provincially and nationally. So it can be suggested that if you want to improve the quality of Qur'an Al Fida pesantren education, then increase the role of leadership.Keywords: Evaluation, Leadership Role, Quality of Education, Pesantren Qur'an Al Fida. Abstrak: Peran kepemimpinan telah mengalami kesulitan sebagai educator, manajer, administrator, supervisor, dan motivator dalam meningkatkan mutu pendidikan, ditandai dengan sebagian kepemimpinan mampu berperan secara baik, dan sebagian yang lain tidak mampu menjalankan perannya seperti kesulitan merekrut murid baru bahkan sekolah mengalami penutupan atau sekolah bubar. Tujuan penelitian ini untuk mengevaluasi peran kepemimpinan dalam meningkatkan mutu pendidikan di Pesantren Qur’an Al Fida. Menggunakan metode deskriptif- kualitatif, dengan pendekatan model CIPP (Conteks, Input, Proses dan Produk). Sumber data primer yang diperoleh melalui pengamatan langsung di lapangan, dan data sekunder yang diperoleh melalui dokumen laporan kepemimpinan pesantren, para wakil, guru-guru, dan tenaga administrasi pesantren melalui wawancara, observasi (pengamatan), dan dokumentasi. Analisis data menggunakan library research, dengan mengkaji, menggumpulkan dan mengolah data dari berbagai sumber literatur, baik jurnal maupun buku. Hasil penelitian menyimpulkan bahwa evaluasi peran kepemimpinan dalam meningkatkan mutu pendidikan di Pesantren Qur’an Al-fia. Tahap contex telah di laksanakan peran kepemimpinannya. Tahap input pimpinan pesantren memberikan pengaruh baik yaitu, memberikan keteladanan hidup, memperhatikan, mengembangkan potensi tenaga kependidikan dan guru, melalui pendidikan dan pelatihan baik seminar, workshop, webinar, memberikan motivasi dan visi misi kedepan yang lebih baik. Tahap proses, pimpinan pesantren melakukan penyesuaian antara program-program yang telah di rencanakan untuk meningkatkan mutu pendidikan di antaranya adalah peningkatan kinerja guru, melibatkan siswa. Tahap produk, telah melaksanakan program peningkatan kinerja guru, belajar yang nyaman bagi siswa, sehingga siswa berprestasi baik provinsi maupun nasional. Sehingga dapat disarankan jika ingin meningkatkan mutu pendidikan pesantren Qur’an Al Fida, maka tingkatkan peran kepemimpinan.Kata kunci: Evaluasi, Peran Kepemimpinan, Mutu Pendidikan, Pesantren Qur’an Al Fida.